Human Capital Relation with Welfare in Indonesia and Asean Countries - Muhammad Ghafur Wibowo (Economics Development Analysis Journal, 2019)
The quality of human capital strongly determines the economic development of a country. Human capital can be shaped by the level of education and public health. This research analyzes the development and competition of human capital of Indonesia and other 5 ASEAN countries from 1985-2016. The problem of this study is whether human capital can be a significant determinant of economic welfare (per capita income) in ASEAN countries. The research used a regression analysis of panel data (all countries) and multiple linear regression (for each country). The independent variables are life expectancy, population growth rate, working-age population, and infant mortality rate per 1,000 live births. The results show that in general, all independent variables have a significant effect on GDP per capita. Nevertheless, an analysis in each country shows different levels and direction of influence. The quality of the human capital of Indonesia is still at the middle level among ASEAN countries. Therefore a variety of efforts to improve the quality of human capital needs to be done by the government and the people of Indonesia to win the competition between ASEAN countries.